The analysis of biohydrogen fuel storing processes - Biernat, Krzysztof; Gołębiowska, Sylwia (Studia Ecologiae et Bioethicae, 2010)
Possibilities of biohydrogen fuel storing were represented. Hydrogen can be store in gas, liquid, or constant form. Technological, material, and economic hydrogen storing determinates were shown. Experiments and researches on finding optimal hydrogen storage methods have been taken into consideration.